2020
DOI: 10.20944/preprints202005.0234.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Epidemiological Challenges in Pandemic Coronavirus Disease (COVID-19): Role of Artificial Intelligence

Abstract: World is now experiencing a major health calamity due to the coronavirus disease (COVID-19) pandemic, caused by the severe acute respiratory syndrome coronavirus clade 2 (SARS-CoV- 2). The foremost challenge facing the scientific community is to explore the growth and transmission capability of the virus. Use of artificial intelligence (AI), such as, deep learning, in (i) rapid disease detection from x-ray/computerized tomography (CT)/ high-resolution computed tomography (HRCT) images, (ii) accurate prediction… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
(82 reference statements)
0
2
0
Order By: Relevance
“…AI is not yet playing a significant role in the fight against COVID-19. Dasgupta et al [55] 2020 et al [57] 2020 Global Global Results of this cohort study showed that the spatiotemporal spread of reported COVID-19 cases could be predicted at a global level by analyzing openly available geolocated Twitter social media data. COVID Near You [58] 2020 US, Canada, Mexico All three countries.…”
Section: Area Captured and Population Effectivenessmentioning
confidence: 90%
“…AI is not yet playing a significant role in the fight against COVID-19. Dasgupta et al [55] 2020 et al [57] 2020 Global Global Results of this cohort study showed that the spatiotemporal spread of reported COVID-19 cases could be predicted at a global level by analyzing openly available geolocated Twitter social media data. COVID Near You [58] 2020 US, Canada, Mexico All three countries.…”
Section: Area Captured and Population Effectivenessmentioning
confidence: 90%
“…Shi et al, used machine learning techniques for data acquisition, diagnosis and prognosis of infected patients. Biological data mining was used to perform COVID-19 detection in (Dasgupta et al, 2020). Another paper (Tayarani N, 2021), discussed the uses of AI in battling COVID-19.…”
Section: Related Workmentioning
confidence: 99%